PENGARUH PEMBERIAN PELATIHAN PENERAPAN SASARAN PATIENT SAFETY BERBASIS APLIKASI MOBILE TERHADAP PERILAKU PERAWAT DI RUANG IGD PUSKESMAS GROGOL SUKOHARJO - Meri Oktariani; Ari Pebru Nurlaily (Jurnal Kesehatan Kusuma Husada, 2019)
Nurses are the largest number of health workers in hospitals and provide 24-hour health services with various nursing procedures and actions. This can provide a great opportunity for errors to occur and threaten patient safety. This is because the hospital has an important role and responsibility in increasing knowledge, skills, behavior and attitudes that are relevant to patient safety. This study aims to analyze the effect of providing patient safety target training on nurse behavior in the application of patient safety targets in the emergency room of the Puskesmas Grogol Sukoharjo. The research method used in this research is a quasy experiment. The sample used was 18 nurses in the Puskesmas Grogol Sukoharjo inpatient room with non-probability sampling techniques and consecutive sampling type. The results of the Wilcoxon test analysis, the value of P value = 0.000 so that the P value <0.05, then H0 is rejected and Ha is accepted that there is an influence of nurse behavior in the application of patient safety after giving training in the application of patient safety. The conclusion of this study is the influence of providing mobile application-based training on nurse behavior in the application of patient safety.